Editorial - Alarcón V., Jorge O. (2014)
The year 2013, under the theme "50 Years of Tropical Medicine in Peru", the Institute of Tropical Medicine Daniel A. Carrión, Faculty of Medicine UNMSM celebrated 50 years of existence. In honor of this important event in the academic life of the School of Medicine, Annals devotes a special section in this issue, which recent research of its members and the review of the First International Institutes of Tropical Medicine are published held in Lima from 12 to 14 June and attended by many national and foreign institutions engaged in research and treatment of health problems of people living in tropical and subtropical areas.